Sir Thomas Elyot as lexicographer - Stein, Gabriele (Oxford University Press, 2014)
Sir Thomas Elyot's Latin-English dictionary, published in 1538, became the leading work of its kind in England. In this book Gabriele Stein describes this pioneering work, exploring its inner structure and workings, its impact on contemporary scholarship, and its later influence. The author opens with an account of Elyot's life and publications. Sir Thomas Elyot (c. 1490-1546) was a humanist scholar and intellectual ally of Sir Thomas More. He was employed by Thomas Cromwell in diplomatic and official capacities that did more to impoverish than enrich him, and he sought to increase his income with writing. His treatise on moral philosophy, 'The Boke named the Governour', was published in 1531 and dedicated to Henry VIII. His popular treatise on medicine, 'The Castell of Helth', went through seventeen editions.